THE INTERCULTURAL INTERPRETATION OF VALUES - M.A. Makhkamova (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the intricate process of understanding values across various cultures, focusing particularly on how language, communication, and worldviews influence these understandings. It investigates how varying cultural backgrounds affect interpretations of fundamental concepts such as respect, freedom, duty, and collectivism, often resulting in misunderstandings or miscommunication during intercultural exchanges. The paper underscores the importance of cultivating intercultural competence through cultural education, empathy, and flexibility to effectively address these challenges. Utilizing examples from both Western and Eastern cultures, as well as the cultural contexts of Uzbekistan and Russia, the study highlights the need for cultural awareness and ethical dialogue to foster mutual understanding. Additionally, the article suggests practical approaches for enhancing intercultural sensitivity in academic, professional, and social settings, thereby contributing to more inclusive and respectful global communication.